Comparative analysis of sustainable productive systems in the Hondurian Mosquitia - Charry, Andres; Claros Trujillo, Luisa María; Bucardo, Elías; Wiegel, Jenny (2023)
The Rio Platano Biosphere Reserve (RPBR) extends over 832 thousand ha in the Mosquitia Region of Honduras, and is one of the most important protected areas of the Mesoamerican biological corridor. Inhabited by indigenous, afro descendant, “colonos” and mestizo communities, who rely on hunting, fishing, livestock, agricultural production and forest use for their livelihoods. The population faces several challenges such as seclusion, lack of access to basic services, tensions between native and incoming communities, land grabbing, deforestation and presence of illicit activities related to drug traffic. The government, NGOs and international cooperation have carried out projects for the development and protection of the region, but the community needs and increasing threats of deforestation are prevalent.